IMPLEMENTASI PENDIDIKAN AGAMA ISLAM BERBASIS AFEKSI DI KOTA YOGYAKARTA - Fahham, Achmad Muchaddam (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2012)
Islamic Religious Education in Public Schools aims at providing an understanding of religion to students and at the same time instilling the noble values of religion and mold them into a person who believes and fear Allah, as well as noble, critical, independent, innovative, tolerant, and responsible. However, the instructional practices of Islamic religious education in schools are likely more important for the mastery of the teachings of Islam and ignore the cultivation of cognitive values and habituation of students to run the Islam religion. The practice is often judged by the observer of education as a form of fundamental weakness of Islamic religious education in schools, because of Islamic religious education instructional practices for students only produce a “good faith” rather than learners who “righteous and noble.” To overcome theweakness of such Islamic religious education instructional practices, the city of Yogyakarta apply affection-based Islamic religious learning in elementary school, junior high schools, and high school. Affection-Based Islamic Religious Education aims at forming students who believe and fear Allah, as well as with morality in school life, family, community, and the State.